Design Of Near Zero Ultra-Flattened Chromatic Dispersion Highly Non Linear Holey Fiber In Tele Communication Band - Rahman, Mahbubur; Mostazir, A.H. Md.; Alam, M. A.; Habib, Md. Samiul (International Journal of Engineering and Technology, 2013)
We propose a four-ring hexagonal holey fiber (HF) which exhibits near zero ultra-flattened chromatic dispersion and nonlinear property simultaneously in a modest number of rings. The finite element method with perfectly matched layers boundary condition is used to investigate the guiding properties. A four ring HF with flattened dispersion of 0.85ps/nm/km from 1.14 to 1.60 µm wavelength range, 21.34W-1km-1 nonlinear coefficient and splice loss 3.82 dB at 1.55µm is numerically demonstrated.